Family resilience in a social-ecological context – emotional difficulties and coping strategies - Vladislav, Elena Otilia; Marc, Gabriela; Paica, Corina-Ioana; Pop, Ovidiu (Frontiers in Psychology, 2024)
Introduction This research explored how crises such as the pandemic influence the family dynamic and the way that the parents and the children face new difficulties and challenges. The present study investigates children’s and young people’s emotional states, the dimensions of family resilience, and the types of coping strategies and parents’ emotional states during the coronavirus pandemic. The final sample for the research was represented by 1,010 parents from Romania. Methods The present scientific research is a transversal study with the scope to understand the emotional difficulties that parents and children/ young people face and the coping strategies that they adopt in a crisis, such as the time of the coronavirus pandemic. Results Parents with maladaptive coping strategies are more affected by the pandemic. Also, the results indicate that there is a significant correlation between parental coping strategies and the children’s emotional states, and the adaptability level. Therefore, the high scores on the subscales which measure maladaptive coping indicate high scores of the levels of depression, anxiety, and stress of the parents. Family resilience, through the dimension of ‘communication and problem-solving in the family’ has a moderation role in the relationship between parental depression and the maladaptive coping strategy of rumination. Family resilience through ‘maintaining a positive attitude’ has a moderation role in the relationship between catastrophizing and the teenagers’ level of adaptability. Discussion The results of the study pointed out the role and place of family resilience within the family system and how a period of crisis can affect this system.